(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, in order to study the socio-philosophical aspects of the need for national unification, it is appropriate to first study the content and classification of the concepts of ideological understanding and national unity in dictionaries. For this reason, the opinion and comments on the clarification of the concept of ideological unity are presented.